Risk factors and outcome of Klebsiella sepsis in neonates - Kantharajanna, Usha B; Niranjan, Hunsanhalli Shivanna; Benakappa, Naveen; Prathik, Bandya (Indian Journal of Child Health, 2020)
Background: Klebsiella is the most common organism isolated in early onset sepsis and causes outbreaks in neonatal intensive care unit (NICU). No clear risk factors for Klebsiella sepsis have been documented. Objective: The objective of the study was to study the risk factors, clinical profile, and outcome of Klebsiella in neonatal sepsis. Materials and Methods: A retrospective observational study was done at an extramural tertiary care center from January to December 2017. After getting Institutional Ethics Committee approval, data were collected from hospital records of admitted neonates whose blood culture was positive for Klebsiella. Detailed antenatal and natal history including birth weight, Apgar score, sex, and age was taken. Data on ventilator support, continuous positive airway pressure, intravenous fluids, enteral and parenteral nutrition, central line, and surgical procedure were collected. Results: Of the total of 1852 blood cultures sent, 308 (16.63%) showed growth. Altogether, 63 (20.45%) cases with Klebsiella growth were included in the study, of which 40 were male and 23 were female (1.7:1). Klebsiella was isolated in 25 (62.5%) who died. Birth weight was 2.152±0.752 g for babies who died and 2.613±0.525 g among discharged. Mortality was high in males 18 (72%) as compared to females 7 (28%), in low birth weight babies 32 (63.69 %), with thrombocytopenia 18 (80%), and those on invasive mode of ventilation. By regression analysis, it was found that duration of days of NICU stay, shock, invasive ventilation, umbilical venous, and arterial catheterization were identified as the factors that influence outcome in Klebsiella sepsis. Conclusion: High index of suspicion, initiating early and appropriate antibiotic therapy, antibiotic stewardship, and environmental cleaning improve the outcome. With emerging drug resistance, prevention of sepsis by infection control measures is needed.